THEORETICAL AND TECHNOLOGICAL BASIS OF CASTING OF HOLLOW BILLETS BY THE METHOD OF DIRECTIONAL SOLIDIFICATION - E. I. Marukovich; V. F. Bevza; A. M. Bodyako; V. P. Grusha (Литьë и металлургия)
The new method of continuously iterative casting of hollow cylindrical castings from cast iron without application of core, based on the principle of direction of metal solidification is presented in the work. the thermal condition of crystallizer at iterative temperature influences on its internal surface and solidification of casting in the conditions of intensive one-way heat sink and presence of constant overheat on front of solidification is examined.